Meningkatkan Perkembangan Bahasa dengan Media Flash Card pada Anak Usia Dini di Desa Sanan Rejo Kabupaten Malang - Dwi Nurhayati Adhani; Nurul Khofifah; Dewi Yuanita (PG-PAUD Trunojoyo, 2016)
Language is always used in everyday life when interacting in society. There is no doubt that language is a major necessity that a person needs for survival. Everyone needs a language to communicate or understand what a person is saying. This study aims to determine the development of language, especially phonology in early childhood through flash card media. This research is done by collecting data from various ways that is observation, interview, documentation. The result of this research can be concluded that in TK.Al-Hikmah Malang there are some children of 5-6 years age range which language development especially phonology experience improvement when using flash card media. From the results of this study, it can be appealed to early childhood educators to apply flash card media to improve the language development of children.